2012
DOI: 10.1371/journal.pone.0031499
|View full text |Cite
|
Sign up to set email alerts
|

RHGF-2 Is an Essential Rho-1 Specific RhoGEF that binds to the Multi-PDZ Domain Scaffold Protein MPZ-1 in Caenorhabditis elegans

Abstract: RhoGEF proteins activate the Rho family of small GTPases and thus play a key role in regulating fundamental cellular processes such as cell morphology and polarity, cell cycle progression and gene transcription. We identified a Caenorhabditis elegans RhoGEF protein, RHGF-2, as a binding partner of the C. elegans multi-PDZ domain scaffold protein MPZ-1 (MUPP1 in mammals). RHGF-2 exhibits significant identity to the mammalian RhoGEFs PLEKHG5/Tech/Syx and contains a class I C-terminal PDZ binding motif (SDV) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 91 publications
3
24
0
Order By: Relevance
“…As previously shown, few let-502 ( sb118ts) embryos arrest between the 1.2- and 2-fold stage at restrictive temperature and the vast majority of the animals hatch as non-elongated larvae (Table 2, line 5, Figure 1A) [10]. 89% and 100% of let-502(sb118ts) embryos arrest between 1.2- and 2-fold stages in pix-1(gk416) and pak-1(ok448) backgrounds, respectively at 25.5°C (Table 2, line 6 and 11).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…As previously shown, few let-502 ( sb118ts) embryos arrest between the 1.2- and 2-fold stage at restrictive temperature and the vast majority of the animals hatch as non-elongated larvae (Table 2, line 5, Figure 1A) [10]. 89% and 100% of let-502(sb118ts) embryos arrest between 1.2- and 2-fold stages in pix-1(gk416) and pak-1(ok448) backgrounds, respectively at 25.5°C (Table 2, line 6 and 11).…”
Section: Resultssupporting
confidence: 58%
“…To assess whether pix-1 also controls early elongation in parallel with the mel-11/let-502 pathway, we tested whether pix-1(gk416) genetically interacts with mel-11(it26) and let-502(sb118ts) temperature sensitive mutants, as reported for pak-1 [3]. At 18°C, 98% of mel-11(it26) mutant embryos rupture during elongation as previously described (Table 2, line 3) [10]. The penetrance of this phenotype is increased to 100% at 25.5°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GTP exchange activity of RHGF-1 resides in the DH domain. Previous studies indicated that RHGF-1 participated in neurotransmitter release (26,28). Consistent with its roles in the nervous system, rhgf-1 was expressed in many neurons in C. elegans, including the PLM (Fig.…”
Section: Significancesupporting
confidence: 67%